Les mangroves face aux changements climatiques : Le cas à la fois typique et particulier du Vietnam - Yann Roche; Pham Van Cu (VertigO)
In the context of climate change and sea level rise, several countries find themselves in a very difficult situation, because of the extent of their coastal zones. This is the case for Vietnam, where most of the 3,200 km of coasts are characterized by a very low elevation, thus very sensitive to sea level rise and storm surges. While initially protecting these areas, the Vietnamese mangroves, like most of the other mangroves all around the world, have suffered huge losses to intensive deforestation. Since the authorities in many countries including Vietnam are now considering the mangrove forests as assets to be protected, the present paper intends to assess the situation of the Vietnamese mangroves through the example of Xuan Thuy National Park, in the Red River Delta. The economic and environmental use of the mangroves is analyzed, as well as their mitigating role regarding climate change and sea level rise. The numerous threats to the ecosystem are seen both in their specificity in the Vietnamese context and as an example of what challenges are now facing the mangroves elsewhere in the tropics. Though mangrove forests are very useful as a buffer area against many natural risks, they don’t seem to be able to play that role against the sea level rise, a threat to which they are more a probable casualty than a viable solution.